Analisis Dampak Usaha Tambak Udang Vanname (Litopenaeus Vannamei) Di Desa Selubuk Kecamatan Air Napal Kabupaten Bengkulu - Ertanto, Bobby; Utama, Satria Putra; Bakhtiar, Deddy; Reflis; Johan, Yar (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
The existence of a new business will have an impact on the physical environment, social, economic and cultural. The purpose of this research is to evaluate the impact of vannamei shrimp farming business on environmental conditions physical and socio-economic conditions of the community. This research was conducted through a survey directly to the research location with stages including literature study, observation, interviews, documentation and data analysis. Water quality tetsing is carried out at UPTD Bengkulu Province DLHK Laboratory and adjusted to the quality standars of PP 22 year 2021. The test results of pH, NH, DO, salinity and odor at the outlet of the sewage pond are not meet quality standards. COD, BOD and color test results at location 1 (one) does not meet the quality standards. Shonnon-Winner Diversity Index Results biological parameters indicate that the water in location 1 (one) was in highly polluted condition and location 2 (two) is in a semi-heavy condition. Factor that cause it to happen the difference in the test results from the two locations is the remaining livestock manure and residual pesticides from plantations/farms around the site. Analysis the socio-economic impact of the community is carried out by Random Sampling through questionnaire to 40 families. The results of analysis of Rank Spearman’s economic impact shows a sufficient relationship. This is evidenced by the existence of a pond business vannamei shrimp there is an increase in the welfare of the community and the development of community-owned businesses. Spearman Rank analysis results social impact shows a strong relationship. Vannamei shrimp farming business is supported by the community because it opens up job opportunities, there is not cultural change socio-cultural community, and there has never been a conflict from community to community company side.